Effects of sodium bicarbonate ingestion on performance and perceptual responses in a laboratory-simulated BMX cycling qualification series - Zabala, M.; Requena, B.; Sanchez-Munoz, C.; Gonzalez-Badillo, J. J.; Garcia, I.; Oopik, V.; Paasuke, M. (The Journal of Strength and Conditioning Research, 2008)
The objective of this study was to examine the effect of sodium bicarbonate (NaHCO3-) ingestion on performance and perceptual responses in a laboratory-simulated bicycle motocross (BMX) qualification series. Nine elite BMX riders volunteered to participate in this study. After familiarization, subjects undertook two trials involving repeated sprints (3 x Wingate tests [WTs] separated by 30 minutes of recovery; WT1, WT2, WT3). Ninety minutes before each trial, subjects ingested either NaHCO3- or placebo in a counterbalanced, randomly assigned, double-blind manner. Each trial was separated by 4 days. Performance variables of peak power, mean power, time to peak power, and fatigue index were calculated for each sprint. Ratings of perceived exertion were obtained after each sprint, and ratings of perceived readiness were obtained before each sprint. No significant differences were observed in performance variables between successive sprints or between trials. For the NaHCO3- trial, peak blood lactate during recovery was greater after WT2 (p < 0.05) and tended to be greater after WT3 (p = 0.07), and ratings of perceived exertion were not influenced. However, improved ratings of perceived readiness were observed before WT2 and WT3 (p < 0.05). In conclusion, NaHCO3- ingestion had no effect on performance and RPE during a series of three WT simulating a BMX qualification series, possibly because of the short duration of each effort and the long recovery time used between the three WTs. On the contrary, NaHCO3- ingestion improved perceived readiness before each WT.